The loneliness of a long-distance runner. A ten-year survey of a patient diagnosed with Gorham-Stout syndrome at the occipitocervical junction - HARMAN, FERHAT (TAYLOR & FRANCIS LTD, 2022)
This case study presents a 47-year-old male who was diagnosed with Gorham-Stout syndrome (GSS) 10 years ago in the occipitocervical junction. The pathology caused the resorption of the suboccipital bone, clivus, foramen magnum, and C1-C3 laminae. After his first fusion attempt in 2010 using occipital plate-cervical lateral mass screws, he needed many revision surgeries either for the progression of the pathology or for instrumentation failure and wound healing problems. Eventually, a new occipital plate and cervical pedicle screws were applied to obtain the exact solution. The involvement of the craniovertebral junction in GSS may be challenging for spinal surgeons due to the inadequate bone reserve for stabilization. As lateral mass screws cannot provide a strong pull-out force, cervical pedicular screws may be used as the first choice for unstable cervical GSS cases.
Keywords: Gorham-Stout syndrome; vanishing bone disease; massive osteolysis; clivus; cranio-cervical junction; MASSIVE OSTEOLYSIS; DISEASE; BONE